Pelatihan Kewirausahaan Perkebunan Durian Di Desa Marisi Dengan Pendekatan Social Entrepreneurship Theory - Siregar, Muhammad Rifai (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2023)
Community service through entrepreneurship training assistance and business development analysis of durian plantations is a program that aims to improve the abilities and skills of farmers and entrepreneurs in the field of durian plantation business. This program is carried out through structured and sustainable training and mentoring activities and is carried out with a participatory and community-based approach. In this program, participants are provided with training and mentoring in various aspects of the durian plantation business, such as financial management, production management, marketing, and business development. Through this program, participants are expected to develop their durian plantation business better and more effectively, so as to increase the productivity and quality of durian produced, as well as open wider market opportunities. The program is also expected to improve the welfare of local farmers and entrepreneurs and contribute to the regional economy. The results of the program evaluation showed that this durian business development analysis and training mentoring program had a positive impact on the participants. The participants claimed to be more confident in managing their businesses, have better knowledge and skills in business management, and are able to develop wider networks and partnerships. In the long run, it is hoped that this program can help increase the business potential of durian plantations in Indonesia